The Importance of Pancasila as a System and Source of Political Ethics in Indonesia - Stefany, Rosa Angela; Waspiah, Waspiah (Universitas Negeri Semarang, 2021)
Ethics is the study of what is good and what is bad. Ethics consists of moral values that guide the life of a person or a group. Politics is an event, activity, or process that involves the government and society in a country in making policies, decisions, or distributing value (in the form of goods and services) to realize the welfare and survival of the community, nation and state. Pancasila is the basis of the state and the ideology of the nation. Value is an unreal quality because it does not exist for itself, value requires a bearer to exist. The values contained in Pancasila are the basis of a system of political ethics. Political ethics based on Pancasila is political ethics in accordance with the values contained in Pancasila. Pancasila as the basis of the political ethics system means that Pancasila is the unity of the precepts, where the Pancasila precepts are a source of political ethics that must always be colored and practiced in the political life of the Indonesian nation. Pancasila is a source of moral ethics, especially in relation to the legitimacy of power, law, and various policies in the implementation and administration of the State.